การใช้ไฟฟ้าอย่างเหมาะสมของพนักงานการไฟฟ้านครหลวง - นีรนุช วลัญช์เสถียร (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
This research studies proper electric power consumption and factors affecting the consumption, of the Metropolitan Electricity Authority officials. Multiple causality approach which is utilized in explaining proper electric power consumption includes intra individual factors (sex, age, knowledge on proper electric power consumption, attitude toward proper electric power consumption, benefit expectation from proper electric power consumption and media exposure to proper electric power consumption) and extra individual factors (education, income and family size). Three hundred and forty-nine Metropolitan Electricity Authority officials are selected by Multi-stage sampling. The questionnaires are administered by the respondents themselves. Simple Regression Analysis, Multiple Regression Analysis and Stepwise Multiple Regression Analysis are used to analize the collected data. The proper electric power consumption behavior of the Metropolitan Electricity Authority officials is a fairly good level. Simple Regression Analysis indicates that age, knowledge on proper electric power consumption, attitude toward proper electric power consumption and income, each has a positive influence on proper electric power consumption, whereas sex has a negative influence on proper electric power consumption at 0.05 significance level. Multiple Regression Analysis reveals that a group of 9 independent variables significantly explain the variation of proper electric power consumption by 15.7 percent. Stepwise Multiple Regression Analysis shows that knowledge on proper electric power consumption has most influence on proper electric power consumption by 8.2 percent, followed by attitude toward proper electric power consumption, education and age which increase the explanatory power by 3.3, 2.5 and 1.0 percent, respectively, whereas other remaining independent variables do not increase the explanatory power the variation of proper electric power consumption at 0.05 significance level.